Chitosan nanofiber scaffold improves bone healing via stimulating trabecular bone production due to upregulation of the Runx2/osteocalcin/alkaline phosphatase signaling pathway - Ho MH (Dove Medical Press, 2015)
Ming-Hua Ho,1,2 Chih-Jung Yao,3 Mei-Hsiu Liao,4 Pei-I Lin,4 Shing-Hwa Liu,5 Ruei-Ming Chen2,4,6 1Department of Chemical Engineering, National Taiwan University of Science and Technology, 2Cell Physiology and Molecular Image Research Center, Taipei Medical University-Wan Fang Hospital, 3Department of Internal Medicine, School of Medicine, 4Graduate Institute of Medical Sciences, College of Medicine, Taipei Medical University, 5Institute of Toxicology, College of Medicine, National Taiwan University, 6Anesthetics and Toxicology Research Center, Taipei Medical University Hospital, Taipei, Taiwan Abstract: Osteoblasts play critical roles in bone formation. Our previous study showed that chitosan nanofibers can stimulate osteoblast proliferation and maturation. This translational study used an animal model of bone defects to evaluate the effects of chitosan nanofiber scaffolds on bone healing and the possible mechanisms. In this study, we produced uniform chitosan nanofibers with fiber diameters of approximately 200 nm. A bone defect was surgically created in the proximal femurs of male C57LB/6 mice, and then the left femur was implanted with chitosan nanofiber scaffolds for 21 days and compared with the right femur, which served as a control. Histological analyses revealed that implantation of chitosan nanofiber scaffolds did not lead to hepatotoxicity or nephrotoxicity. Instead, imaging analyses by X-ray transmission and microcomputed tomography showed that implantation of chitosan nanofiber scaffolds improved bone healing compared with the control group. In parallel, microcomputed tomography and bone histomorphometric assays further demonstrated augmentation of the production of new trabecular bone in the chitosan nanofiber-treated group. Furthermore, implantation of chitosan nanofiber scaffolds led to a significant increase in the trabecular bone thickness but a reduction in the trabecular parameter factor. As to the mechanisms, analysis by confocal microscopy showed that implantation of chitosan nanofiber scaffolds increased levels of Runt-related transcription factor 2 (Runx2), a key transcription factor that regulates osteogenesis, in the bone defect sites. Successively, amounts of alkaline phosphatase and osteocalcin, two typical biomarkers that can simulate bone maturation, were augmented following implantation of chitosan nanofiber scaffolds. Taken together, this translational study showed a beneficial effect of chitosan nanofiber scaffolds on bone healing through stimulating trabecular bone production due to upregulation of Runx2-mediated alkaline phosphatase and osteocalcin gene expressions. Our results suggest the potential of chitosan nanofiber scaffolds for therapy of bone diseases, including bone defects and bone fractures. Keywords: chitosan nanofibers, bone healing, micro-computed tomography, bone histomorphometry, Runx2/OCN/ALP